Application of Indigenous Knowledge in Building Resilience: A Case Study of the Construction of Bayan Traditional Houses in Lombok - Sariadi, Sariadi; Kurnia, Nova; Sukarma, I Ketut; Herayanti, Lovy; Habibi, Habibi; Azmi, Irham (Universitas Pendidikan Mandalika, 2023)
The Bayan traditional house in Lombok, West Nusa Tenggara, exemplifies traditional architecture that integrates Indigenous Knowledge (IK) in building construction. This study aims to analyze the construction techniques of the Bayan traditional house in enhancing earthquake resistance and environmental adaptation while exploring its potential application in sustainable modern architecture. A qualitative research approach with a case study design was employed, incorporating participant observation, in-depth interviews with key informants, and document and visual analysis. Findings reveal that Bayan traditional houses utilize distinctive construction techniques such as nail-free wooden joinery, flexible local materials like bamboo and hardwood, and thatched roofs that adapt to tropical climates. These techniques enhance structural flexibility in absorbing seismic shocks while providing optimal thermal efficiency and natural ventilation. These findings align with previous studies indicating that IK-based structures demonstrate greater resilience compared to modern concrete buildings. This study asserts that IK principles in Bayan traditional houses can be integrated into contemporary architectural design to create more environmentally friendly and disaster-resilient buildings. Therefore, policies promoting the adoption of IK-based construction techniques in modern housing and infrastructure development are essential to enhance sustainability and disaster preparedness in the future.